Triticale: today and tomorrow: [... papers presented at the Third International Triticale Symposium held in Lisbon, Portugal ...] - Guedes-Pinto, Henrique; Darvey, Norman; Carnide, Valdemar P. (Developments in plant breeding, 1996)
Triticale's days as a scientific curiosity are definitely over. Its wide acceptance as a feed, grain or forage crop, or for baking and malting, plus its high yields under marginal or stress conditions have made it an economically important crop in countries such as Poland, Germany, Australia, Portugal, Brazil, Morocco and China. This publication contains selected, reviewed, and up-to-date papers presented at the Third International Triticale Symposium held in Lisbon, Portugal, by the International Triticale Association and EUCARPIA. Among the broad spectrum of subjects addressed in these presentations are cytogenetics, biotechnology, genetic resources, breeding, agronomic practices and diseases. Also included are triticale's food, feed and forage uses, as well as its marketing processes. In a world of increasing population and decreasing agricultural resources, triticale offers a genuine solution for increasing land utilization and grain production